Optimalisasi Potensi Desa Dengan Menumbuhkan Jiwa Kewirausahaan Masyarakat Desa - Ismail; Ilham, Ilham; Wahyuni, Nur Wahyuni; Kessi, Andi Muhammad Fara; Husain, Ahmad (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
Every village basically has natural potential that can be managed and utilized optimally. Natural potential that can be utilized to be used as a business (Entrepreneurship) for survival to be more prosperous. In the current millennial era, of course, almost every community living in a particular village is less aware of the potential of their village for entrepreneurship and has not been able to utilize natural potential optimally. Moreover, Processing and innovating products to be pioneered. Efforts to encourage people to become entrepreneurs and foster an entrepreneurial spirit in the village are considered important. Balangtanaya Village is one of the villages in the North Polongbangkeng District, Takalar Regency which has a lot of natural potential and is a village famous for its agricultural products. In the implementation of Community Service activities, Group 6 created an activity with the topic of Optimizing Village Potential by Cultivating the Entrepreneurial Spirit of the Balangtanaya Village Community whose scope of activities responds to the community so that they are able to become entrepreneurs and utilize the natural potential in the village. An activity program that seeks to synergize between utilizing nature and processing products to become productive businesses in Balangtanaya Village.